Uganda: contradictions of the IMF programme and perspective - Mutebile, Emmanuel Tumusiime (Willey, 1991)
In his article ‘Uganda: Contradictions of the IMF Programme and Perspective’, published in Development and Change in July 1990, Professor Mamdani sought to criticize the stabilization and structural adjustment programme in Uganda through its immediate economic consequences; through a longer term historical analysis raising more fundamental issues of social transformation; and through a comparative discussion using South East Asian development experience (Mamdani, 1990: 427). Considerations of space limit the scope of this comment to pointing out that the economic analysis of his article is weak and, in particular, the analysis of the effect of official exchange rate devaluation is incorrect. However, because his analysis of the economics of stabilization underpins the analysis of wider social issues, the faulty economic analysis calls into question the validity of his overall conclusions. The economic crisis in Uganda is the cumulative result of specific events since the early 1970s - albeit in a wider historical context. But the immediate problem in Uganda is economic: a severe fiscal crisis combined with a persistently fragile balance of payments position. Such disequilibria are unsustainable and must be corrected. With or without the IMF, no country can escape the constraint of making ends meet. It is essential that this process of adjusting to meet changed circumstances takes place in an orderly manner so that the benefits of managed change are realized at least cost to
: a comment
Keywords: Uganda; IMF programme; Contradictions